Municipal solid waste-based district heating and electricity production: A case study. (15th May 2021) - Tozlu, Alperen; Abusoglu, Aysegul; Ozahi, Emrah; Anvari-Moghaddam, Amjad
Abstract: In this paper, municipal solid waste (MSW) based electricity production and district heating (DH) potential of Turkey are considered. Three MSW based waste-to-energy (WtE) scenarios is developed: (i) Scenario-I, a DH system integrated into a gas turbine power plant (GTPP), (ii) Scenario-II, a DH system integrated into an organic Rankine cycle (ORC), and (iii) Scenario-III, which is based solely on a DH system. As a result of the thermodynamic and thermoeconomic analyzes of these developed scenarios using an existing MSW-based cogeneration facility's actual operating data, the system with the most extended payback period (about 5 years) is found as the GTPP-DH system developed in Scenario-I, which also has the highest investment cost. On the other hand, the system with the shortest payback period (about 2 years) is found as the DH system developed in Scenario-III, which also has the lowest investment cost. Overall exergy efficiencies of the GTTP-DH, ORC-DH, and DH systems are found to be 41.86%, 16.15%, and 31.87%, respectively. When the developed WtE scenarios adapted to the pilot provinces selected from each geographical region of Turkey, it is found that the GTPP system developed in Scenario-I can increase the power generation capacity of MSW plants for each province by about 20%. Highlights: DH and electricity production potentials of the MSWPs are considered. Three MSWP based WtE scenarios are developed: GTPP-DH, ORC-DH, DH network. Heat demand of 4344 dwellings can be met with DH system developed in Scenario I. Heat demand of 946 dwellings can be met with DH system developed in Scenario II. Heat demand of 7069 dwellings can be met with DH system developed in Scenario-III.